2003
DOI: 10.1002/pc.10056
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical property improvement of carbon fiber reinforced polybenzoxazine by rubber interlayer

Abstract: The rubber interlayer method was chosen in order to improve the properties of carbon fiber‐reinforced polybenzoxazine composites. The resin used is benzoxazine based on bisphenol‐A, formaldehyde and 3,5‐xylidine. The effect of rubber concentration on the flexural properties of the composites is investigated. Sized and desized carbon fiber woven fabrics are used to study the effect of the sizing materials on the mechanical properties. The delamination toughness of the composites is increased by the ATBN rubber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…The concept of a uniform, thin low‐modulus layer at the fiber–matrix interface describing the unexpected lower values of modulus in some thermoset‐matrix composite systems has recently been found as a potential basis for explaining the antagonistic effects in NF‐modified MFC . In this study, the original FEA model (Figure , Table ) has been modified to comply with the character of crystallinity in polymers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of a uniform, thin low‐modulus layer at the fiber–matrix interface describing the unexpected lower values of modulus in some thermoset‐matrix composite systems has recently been found as a potential basis for explaining the antagonistic effects in NF‐modified MFC . In this study, the original FEA model (Figure , Table ) has been modified to comply with the character of crystallinity in polymers.…”
Section: Resultsmentioning
confidence: 99%
“…This may lead to a corresponding different degree of NF localization and ordering in the interfacial area, which may affect the crystallinity of both polymer components. The importance of the changed parameters of the interface consists, for example, in the fact that the presence of a very thin low‐modulus layer at the fiber surface can decrease the composite modulus significantly, as shown for high‐modulus fiber/epoxy composites …”
Section: Introductionmentioning
confidence: 99%
“…One of the most effective methods is by coating the carbon fibers with a ductile polymeric material to modify the mode of failure and thus the potential energy absorbing capacity of their composites [5][6][7]. However, many researches showed that thin coatings were finite in toughening the composites whereas thick coatings resulted in the reduction of composite strength and modulus [8,9]. In our previous study [10][11][12][13], similar results showing that the prolongation of the flexible blocks increased the thickness of the flexible layer and as a result the interfacial shear strength decreased due to the low cohesive strength and modulus of the flexible chains, were also obtained.…”
Section: Introductionmentioning
confidence: 99%
“…During the Vietnam War, it was reported that soft armors prepared from fabrics of fiber glass and nylon were used for ballistic protection [3]. Some of the commercial fibers used to manufacture armors include aramids (Kevlar TM or Twaron TM ) [4], nylon fiber [5], polyethylene fiber (Spectra TM or Dyneema TM ) [6,7], and carbon fiber [8,9]. The fibers should provide excellent impact resistance required for ballistic armors, and have high sonic velocity and high specific energy absorption as well as the capability to distribute kinetic energy upon ballistic impact [5].…”
Section: Introductionmentioning
confidence: 99%